Studying illegal online trades in plants: market characteristics, organisational and behavioural aspects, and policing challenges - Lavorgna, Anita (European journal on criminal policy and research, 2021)
Illegal commerce in plants and their derivatives threatens and destroys numerous species and important natural resources, and may cause phytosanitary and health problems. This illegal trade, which has been boosted by the commercialisation of the Internet, has been relatively overlooked in criminological research. Furthermore, the policing of illegal plant markets remains limited and poorly resourced, with law enforcement agencies lacking awareness and technical capacity in investigation and prosecution services. Based on semi-structured interviews with law enforcement officers and other relevant experts, this study, developed in the context of the ESRC-funded project “FloraGuard: Tackling the illegal trade in endangered plants” offers an analysis of the characteristics of illegal online trading in plants and of the actors operating therein, of current policing practices, and identification of the main challenges to be addressed to better assist law enforcement. It concludes by offering practical recommendations to curb this illegal market.